Modeling and analyzing the dynamics of brucellosis disease with vaccination in the fractional derivative under real cases - Al-Hdaibat, Bashir; Khan, Muhammad Altaf; Ahmad, Irfan; Alzahrani, Ebraheem; Akgul, Ali (Springer Nature, 2025)
The present explores the brucellosis model in non-integer derivative by utilizing the real statistics from the mainland China. The formulation of the model first presented in integer order derivative and subsequently extended to fractional order using the Caputo derivative. The existence and uniqueness of the nonlinear fractional system is confirmed, which is the important requirement for a fractional nonlinear model. The local asymptotical stability of the fractional model when R0<1 is analyzed. When R0≤1, the model is found globally asymptotically stable. The existence of an endemic equilibria is given and found that the model has a unique endemic equilibrium. Using the reported cases of brucellosis in mainland China from 2004 to 2018 are considered. Graphical results for data fitting in cumulative and daily wise are presented with their respective residuals. The basic reproduction number is obtained from data fitting is R0=1.0327. A numerical scheme for the Caputo case is provided in detailed and later the scheme was used to obtain the numerical results graphically. Various results regarding the disease curtail are presented graphically, that will be helpful for the disease elimination in the long run. The public health authority and the health agencies can utilize this work confidently for brucellosis control in mainland China.